New insights on molybdenum fertilization in common bean under no-tillage system: rates and application time to obtain high vigor seeds - Silva, Marcio Souza da [UNESP]; Oliveira, Gustavo Roberto Fonseca de [UNESP]; Merloti, Luís Fernando; Bossolani, João William [UNESP]; Camargos, Liliane Santos de [UNESP]; de Sá, Marco Eustáquio [UNESP]; Reis, André Rodrigues dos [UNESP] (Taylor & Francis, 2020)
Molybdenum (Mo) is a key element in the N fixing and assimilation processes in leguminous plants. This study aimed to evaluate the effects of Mo fertilization on the yield and seed vigor of the common bean. Molybdenum was applied at six rates (0, 20, 40, 80, 120 and 160 g ha−1) in field trials over 2 consecutive years (2015 and 2016). Foliar applications were performed during the phenological stages V4 (4th trifoliolate leaf unfolded) and R1 (early flowering). The SPAD index, height of first pod insertion, number of pods per plant, number of seeds per pod, weight of 100 seeds, yield and seed vigor were determined. Molybdenum affected the production of reproductive organs only in the second agricultural year. Application of Mo at T-V4 resulted in an increase in the number of pods per plant (11%), and at 120 g ha−1, there was an increase (41%) in the number of seeds per pod, but this did not result in a yield seed increase. Molybdenum applied at the T-V4 phase reduced electrical conductivity in the first year of the experiment at rates of 40 g ha−1 (17%) and 160 g ha−1 (13%). In the second agricultural year, Mo applied at the T-R1 phase reduced in 44% the electrical conductivity, as well as the application of 20 g ha−1 also at the T-R1 phase increased seed germination (28%), seedling length (8%), and length of the primary root (10%). Different responses to the Mo application time and dose between the experimental years suggest that common bean plants recycle Mo. Molybdenum applied in the first agricultural year may have satisfied the initial Mo demand of the common beans in the second year of crop due it's low Mo requirement. This study show that foliar Mo application is an important strategy to achieve sustainable production of higher quality seeds of common bean.
Keywords: crop yield; no-tillage system; Phaseolus vulgaris L; rate of fertilization; seed production; time of fertilization